The Relationship Between Drug Prevention Campaigns And Awareness To Reduce The Addiction Phenomenon Among College Students In UAE - Alkatheeri, Helal Bader Omar Abdulla (2023)
The present study focuses on the national anti-drug abuse campaign championed by key actors such as the National Rehabilitation Center (NRC), Police Departments, other governmental and non-government organisations. The study considers the positivist research philosophy in a quantitative research methodology, deductive research approach, and survey research strategy.